2017
DOI: 10.4236/wjcd.2017.72005
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes for Abdominal Obesity Prevention and Encouraging Fruit Consumption May Be Beneficial in Preventing Left Ventricular Hypertrophy in Sub-Saharan African and Maghreb

Abstract: There is a growing body of evidence showing a close correlation between left ventricular mass with cardiovascular morbidity and overall mortality. Therefore, identifying the determinants of left ventricular hypertrophy can be of great importance for cardiovascular prevention, for prognosis and therapeutic intervention. Objective: To assess the prevalence and identify the independent determinants of echocardiographic left ventricular hypertrophy in The MAGhreb and Sub-Saharan Africa Left-Ventricul ArGEometry St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Focusing on isolated nutrients certainly cannot account for all interactions and may result in erroneous conclusions [101], but research focusing on single foods items could improve mechanistic understanding of the effects of diet patterns [100]. In a previous biracial population based study, we found that reduced fruit consumption was independently and significantly associated with echocardiographic LVH [102]. Studies have shown an inverse association between fruit consumption and the risk of cardiovascular events [25,103].…”
Section: Sci Forschenmentioning
confidence: 77%
“…Focusing on isolated nutrients certainly cannot account for all interactions and may result in erroneous conclusions [101], but research focusing on single foods items could improve mechanistic understanding of the effects of diet patterns [100]. In a previous biracial population based study, we found that reduced fruit consumption was independently and significantly associated with echocardiographic LVH [102]. Studies have shown an inverse association between fruit consumption and the risk of cardiovascular events [25,103].…”
Section: Sci Forschenmentioning
confidence: 77%
“…In reality, this overlooks the relationship between LV volume and wall thickness. The 2015 ASE guidelines for chamber quantification[29] describe a normal LV wall thickness (IVS or PW) as 0.6 -1.0 cm for males and 0.6 -0.9 cm for females. An increased wall thickness may be suggestive of LVH, but as an isolated number it gives no information about LVM or LV modeling.…”
mentioning
confidence: 99%